A Survey of Biology Teachers Use of Activity-Oriented, Laboratory Practical Exercises to Promote Functional Biology Education - Abigail Mgboyibo Osuafor; Ijeoma A. Amaefuna (Intelektual Pustaka Media Utama, 2016)
A major goal of science education is fostering students’ intellectual competencies such as independent learning, problem-solving, decision-making and critical thinking. This goal can only be achieved when students are actively involved in the teaching-learning process through activity-based, practical-oriented instructional methods involving the use of laboratories. This study therefore, investigated the extent to which the biology teachers employ activity-oriented, laboratory/practical instructional methods in order to improve the learning outcome of their students. The descriptive survey involved 73 Biology teachers randomly selected from all the six education zones of Anambra state, Nigeria. Four research questions were posed and four hypotheses were formulated to guide the conduct of the study. A 32-item structured questionnaire which has reliability co-efficient of 0.82 was used to collect data. Data were analyzed using mean, standard deviation and t-tests. Results show that Biology teachers adopt practical-oriented strategies in teaching biology, conduct practical activities to a high extent, and perceive practical exercises as essential to effective teaching and learning of the subject. Provision of adequate number of laboratory materials, employment of adequate number of biology teachers, making provision for well designed laboratory activities in the curriculum and training of teachers on how to effectively combine theory with practical are some of the strategies that will encourage biology teachers to conduct practical lessons. There was no significant difference between male and female biology teachers in their responses to the different aspects investigated. Based on these findings, some recommendations were made that include that curriculum designers should incorporate guides for practical activities that go with each topic in the curriculum so as to encourage the teachers to teach theory with practical as a unified whole to increase students’ understanding and internalization of the facts and ideas taught.